2000
DOI: 10.1034/j.1399-0012.2000.140311.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic analysis of endothelial cell coverage and quality in large vessels from multi‐organ donors: effects of preservation on endothelial cell integrity

Abstract: Endothelial cell integrity (coverage and quality) of large donor vessels is important because these vessels are used for vascular reconstructions in solid-organ transplantation. Disruption of the endothelial cell monolayer will initiate blood coagulation and may lead to thrombosis of large vessels, often resulting in the loss of the transplanted organ. Iliac arteries and veins, removed from 10 heart-beating multi-organ donors at the end of the donor procedure, were analyzed using scanning electron microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Cold storage of vascular endothelial cells has been shown to induce increased adhesion of platelets, 36 and storage of vessels has been shown to disrupt the endothelial monolayer. 37,38 Both might lead to thrombosis and graft occlusion, which could result in the loss of the organ/tissue supplied by the grafted vessel. 39,40 In solution 8 with 0.1 mmol/L deferoxamine ϩ 20 mol/L LK 614, the platelet adherence was significantly reduced compared with HTK solution, indicating lower thrombogenicity.…”
Section: Role Of Chloridementioning
confidence: 99%
“…Cold storage of vascular endothelial cells has been shown to induce increased adhesion of platelets, 36 and storage of vessels has been shown to disrupt the endothelial monolayer. 37,38 Both might lead to thrombosis and graft occlusion, which could result in the loss of the organ/tissue supplied by the grafted vessel. 39,40 In solution 8 with 0.1 mmol/L deferoxamine ϩ 20 mol/L LK 614, the platelet adherence was significantly reduced compared with HTK solution, indicating lower thrombogenicity.…”
Section: Role Of Chloridementioning
confidence: 99%
“…In the current study this monolayer was present in the control carotid arteries and could also be demonstrated in the AU grafts. Flat endothelial cells with a smooth surface and without pores and microvilli are criteria for cells in the normal condition [36]. Endothelial cells were flattened in the GL allografts too, comparable with the endothelial cells in the AU.…”
Section: Discussionmentioning
confidence: 99%
“…Before isolation of EC, a tissue sample of 100 mm 2 was removed for scanning electron microscopy, showing varying EC-coverage and quality as described previously (van Leeuwen et al, 2000). Multiplication of the total intimal surface and the percentage of surface covered with EC resulted in the actual EC-surface available for isolation (Table 1).…”
mentioning
confidence: 99%